Søker fortiden og framtiden på Sydpolen - Bakka, Toril (Statoil magasin, 1992)
Keywords: Antarktis; biografi; ekspedisjoner

Atmospheric CO₂ and global warming: a critical review - Jaworowski, Zbigniew; Segalstad, Tom Victor; Hisdal, Vidar (Norsk Polarinstitutt, 1992)
Publication Title: Meddelelser
Keywords: Antarktis; atmosfæren; drivhuseffekten; isbreer; karbondioksid; klimaendringer; klimagasser; paleoatmosfæren; temperaturforhold

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
URL: https://www.researchgate.net/publication/223504148_Do_glaciers_tell_a_true_atmospheric_CO2_story
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Determination of sulphur- and chlorine-containing compounds using capillary gas chromatography and atomic emission detection - Pedersen-Bjergaard, Stig; Asp, Tone Normann; Greibrokk, Tyge (Analytica Chimica Acta, 1992)
The potential of universal calibration using capillary gas chromatography combined with atomic emission detection was evaluated for several chlorine- and sulphur-containing compounds of environmental interest. The elemental responses obtained for C, H, Cl and S were found to be affected by the molecular structure. Rapid determination of several analytes was accomplished using a single calibration graph based on one randomly selected reference compound, but 10–30% errors relative to the actual concentrations were observed in several instances. The results were significantly improved by using reference compounds with structures similar to those of the analytes of interest. the practical utility of universal calibration is illustrated by the determination of pesticides in stomach oil deposits from birds living in Antarctica.
Keywords: Antarktis; biokjemi; fugler; kjemi; kromatografi; petreller

Samtykke til ratifikasjon av Protokoll om miljøvern til Antarktistraktaten, undertegnet i Madrid 4. oktober 1991 - Utenriksdepartementet (1992)
Pages: 64 Place: Oslo
Keywords: Antarktis; forvaltning; miljøvern; politikk

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Publisher: Sandefjordmuseene Place: Sandefjord
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner